Metabolic Syndrome Of Type 2 Diabetes Mellitus - Azizova Shoira Kayumovna; Mardonova Sojidabonu. (Euro Asian Journal Publishing, 2024)
The subsequent development of events in the pathogenesis of DM2 includes increased insulin secretion as a response of the body to a lack of its action. However, prolonged hyperinsulinemia leads to dysfunction of pancreatic β-cells and a decrease in insulin synthesis against the background of persistent IR. As a result, the insulin-dependent transport of glucose from the bloodstream to the cells of muscle and adipose tissues is finally disrupted, glucose synthesis in the liver increases and, accordingly, its secretion into the bloodstream
Keywords: insulin resistance; diabetes mellitus; hyperglycemia